Defining directions for improving public procurement of innovation in the European Union - Davydiuk, Oleksandr; Shvydka, Tetiana; Ostapenko, Iuliia; Tarasov, Oleh; Bytiak, Oleksii (Technology audit and production reserves, 2026)
The object of research is the system of regulatory methods for identifying public procurement in the European Union, as one of the ways to stimulate innovation circulation. The research is aimed at solving the issue of improving the design of this support tool to the updated requirements of the European Union. The directions, methods and methods of improving the institution of public procurement are studied in order to bring it into line with real needs. The study of the processes of regulating public procurement of innovations in the European Union has established their inconsistency with the real needs of participants in innovation circulation. It is proven that these inconsistencies negatively affect the level of support and scaling of innovation processes. The need to improve the regulatory approach to implementing public procurement of innovations in the European Union is substantiated. The introduction of a new procedure for public procurement of innovations – public financial grant support – is proposed. The need to soften the requirements for the mandatory presence of an intellectual property right in the innovation is proven. The need to expand the circle of participants in the procedure for public procurement of innovations is substantiated. The need to amend Directive 2014/24/EU of the European Parliament and of the Council of February 26, 2014, the Horizon Europe Framework Programme; European Innovation Act is identified. The research is aimed at developing general theoretical principles for improving the regulation of public procurement of innovations in the European Union. The results of this research can be used to improve the official rules for the dissemination and circulation of innovations, the formation of relevant decisions of government bodies, state innovation policy and the basis for further scientific research on the specified issues.